Evaluation of service quality and complaint handling on outpatient satisfaction at the pharmaceutical installation of mokoyurli buol regional public hospital - Saputri, Chynthia Iga; Oetari, RA.; Wijayanti, Tri (Universitas Ahmad Dahlan, 2022)
Pharmaceutical installations have an important role in improving and providing effective services to achieve patient satisfaction. Patients' complaints occur if they receive a service that does not meet expectations. The hospital management must investigate the causes of patients' complaints. Solving the patients' complaints indicates that the hospital can fulfill their expectations. The purpose of this study is to examine the results of servqual on service quality, customer satisfaction index, and importance-performance analysis on service quality and complaint handling. This research employed a descriptive design with qualitative and quantitative approaches. The study was conducted by distributing questionnaires to 100 outpatients. The respondents' answers were then analyzed using the Cartesian diagram to obtain quadrants A, B, C, and D. Interviews were directly conducted with the complaint management and pharmaceutical installation staff to explore the attributes included in quadrant A (top priority). The patients were selected using the purposive sampling method. Finally, the data were analyzed using the servqual analysis, importance-performance analysis, and customer satisfaction index. The result shows that the service quality dimension has a negative gap value. The reliability dimension has the smallest gap while the responsiveness dimension has the largest gap. The result of the customer satisfaction index shows that outpatient satisfaction with the service quality and complaint handling has a value of 56.53%. Thus, this dimension is categorized as quite satisfying. The result of the importance-performance analysis shows that the dimensions included in quadrant A are the tangible evidence dimension, including poor physical facilities, and the responsiveness dimension, including patients' long waiting time to manage prescriptions and complaint handling.